North Carolina and World War II : a documentary portrait - Davis, Anita Price (McFarland & Company, Inc., Publishers, 2014)
"This Southern state trained more troops than any other state in the nation. Can one still find the military posts and shipyards, the cemeteries and memorials, the convalescent units and R & R facilities today? This volume describes in detail both the state's 20-plus military sites and the eight little-known North Carolina Prisoner of War camps"--